The Influence of Spirulina platensis Filtrates on Caco-2 Proliferative Activity and Expression of Apoptosis-Related microRNAs and mRNA - Agnieszka Śmieszek (Marine Drugs, 2017)
Spirulina platensis (SP) is a blue-green microalga that has recently raised attention not only as a nutritional component, but also as a source of bioactivities that have therapeutic effects and may find application in medicine, including cancer treatment. In the present study we determined the cytotoxic effect of S. platensis filtrates (SPF) on human colon cancer cell line Caco-2. Three concentrations of SPF were tested—1.25%, 2.5%, and 5% (v/v). We have found that the highest concentration of SPF exerts the strongest anti-proliferative and pro-apoptotic effect on Caco-2 cultures. The SPF negatively affected the morphology of Caco-2 causing colony shrinking and significant inhibition of metabolic and proliferative activity of cells. The wound-healing assay showed that the SPF impaired migratory capabilities of Caco-2. This observation was consistent with lowered mRNA levels for metalloproteinases. Furthermore, SPF decreased the transcript level of pro-survival genes (cyclin D1, surviving, and c-Myc) and reduced the autocrine secretion of Wnt-10b. The cytotoxic effect of SPF involved the modulation of the Bax and Bcl-2 ratio and a decrease of mitochondrial activity, and was related with increased levels of intracellular reactive oxygen species (ROS) and nitric oxide (NO). Moreover, the SPF also caused an increased number of cells in the apoptotic sub-G0 phase and up-regulated expression of mir-145, simultaneously decreasing expression of mir-17 and 146. Obtained results indicate that SPF can be considered as an agent with anti-cancer properties that may be used for colon cancer prevention and treatment.